2021
DOI: 10.1103/physreve.104.014702
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of capillary coalescence and breakup: Quasi-two-dimensional nematic and isotropic droplets

Abstract: For the first time we observed Rayleigh-Plateau instability with formation of satellite domains at droplet coalescence. Investigations were made using a Hele-Shaw cell in the twophase region at nematic-isotropic phase transition. In previous works on quasi-2D coalescence it was considered that before start of coalescence there exists a bridge between the outer fluid connecting regions on the two sides of the droplets (outer bridge). After start of coalescence a bridge connecting the two droplets appears (dropl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Copyright 2011 by National Academy of Sciences. Dolganov et al observed the same power-law scaling relation (r~t 1/4 ) as Yokota and Okumura for the coalescence of two drops of liquid crystal E7 occurring in a Hele-Shaw cell (D = 5-50 µm)[41]. In their study, coalescence occurred between two quasi-2D drops, not between a drop and a bath.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Copyright 2011 by National Academy of Sciences. Dolganov et al observed the same power-law scaling relation (r~t 1/4 ) as Yokota and Okumura for the coalescence of two drops of liquid crystal E7 occurring in a Hele-Shaw cell (D = 5-50 µm)[41]. In their study, coalescence occurred between two quasi-2D drops, not between a drop and a bath.…”
mentioning
confidence: 62%
“…Chinaud et al observed that the bridge grew linearly with time (i.e., r~t) irrespective [41]. In their study, coalescence occurred between two quasi-2D drops, not between a drop and a bath.…”
Section: Coalescence Of Drops In Hele-shaw Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…The round, or even circular, meniscus profile was expected because of the small gap height of the Hele-Shaw cell (i.e., Bo < 1). Similarly, Dolganov et al found that the cross-sectional meniscus profile of a liquid crystal drop in a Hele-Shaw cell was close to circular [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to compare our experiment with the coalescence of isotropic droplets separated by a nematic bridge of the same material in flat cells. This scenario was studied by Dolganov et al 93,94 The situation is different there because the experiments were performed in Hele-Shaw cells. The presence of the upper and lower glass plates changes the situation completely.…”
Section: Conflicts Of Interestmentioning
confidence: 99%